Nigerian administrative law - Oluyede, Peter (Ibadan : University Press, 1988)
This book provides insight into the the administrative justice fundamentals for students, teachers and administrators of the bar and bench.
Includes bibliographical references.
asm; 30/09/19
Loans
Keywords: Administrative law; Administrative procedure; Judicial review of administrative acts; Local government